THE ROLE OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR BASED ON SPIRITUAL QUOTIENT AND SELF EFFICACY ON THE PERFORMANCE OF CV ALIANSYAH PATI EMPLOYEES - Pipit Larasati; Miladia Fadilasari; M Fatchurrohman (Universitas Wahid Hasyim Semarang, 2024)
This research aims to determine and analyze the influence of spiritual quotient and self-efficacy on employee performance with organizational citizenship behavior as an intervening variable. The population in this study were all CV employees. Aliansyah Pati was 105. Based on the results of distributing questionnaires to all employees, a sample size of 98 people was obtained. The analysis tool used is Partial Least Square.The research results show that the spiritual quotient and self-efficacy are able to bring about better changes in improving employee behavior to be willing to work extra towards their work. Spiritual quotient, self-efficacy and organizational citizenship behavior are also able to provide better changes in improving employee performance. Organizational citizenship behavior has been proven to be an intervening variable between spiritual quotient and employee performance. Organizational citizenship behavior has also been proven to be an intervening variable between self-efficacy and employee performance. Key word : Spiritual quotient, self efficacy, organizational citizenship behavior, employee performance